Chloroplast Redox Status Modulates Genome-Wide Plant Responses during the Non-host Interaction of Tobacco with the Hemibiotrophic Bacterium Xanthomonas campestris pv. vesicatoria - Pierella Karlusich, Juan J.; Zurbriggen, Matias D.; Shahinnia, Fahimeh; Sonnewald, Sophia; Sonnewald, Uwe; Hosseini, Seyed A.; Hajirezaei, Mohammad-Reza; Carrillo, Néstor (Frontiers in Plant Science, 2017)
Non-host resistance is the most ample and durable form of plant resistance against pathogen infection. It includes induction of defense-associated genes, massive metabolic reprogramming, and in many instances, a form of localized cell death (LCD) at the site of infection, purportedly designed to limit the spread of biotrophic and hemibiotrophic microorganisms. Reactive oxygen species (ROS) have been proposed to act as signals for LCD orchestration. They are produced in various cellular compartments including chloroplasts, mitochondria and apoplast. We have previously reported that down-regulation of ROS build-up in chloroplasts by expression of a plastid-targeted flavodoxin (Fld) suppressed LCD in tobacco leaves inoculated with the non-host bacterium Xanthomonas campestris pv. vesicatoria (Xcv), while other defensive responses were unaffected, suggesting that chloroplast ROS and/or redox status play a major role in the progress of LCD. To better understand these effects, we compare here the transcriptomic alterations caused by Xcv inoculation on leaves of Fld-expressing tobacco plants and their wild-type siblings. About 29% of leaf-expressed genes were affected by Xcv and/or Fld. Surprisingly, 5.8% of them (1,111 genes) were regulated by Fld in the absence of infection, presumably representing pathways responsive to chloroplast ROS production and/or redox status during normal growth conditions. While the majority (~75%) of pathogen-responsive genes were not affected by Fld, many Xcv responses were exacerbated, attenuated, or regulated in opposite direction by expression of this protein. Particularly interesting was a group of 384 genes displaying Xcv responses that were already triggered by Fld in the absence of infection, suggesting that the transgenic plants had a larger and more diversified suite of constitutive defenses against the attacking microorganism compared to the wild type. Fld modulated many genes involved in pathogenesis, signal transduction, transcriptional regulation and hormone-based pathways. Remarkable interactions with proteasomal protein degradation were observed. The results provide the first genome-wide, comprehensive picture illustrating the relevance of chloroplast redox status in biotic stress responses.